Identification of by-products of fermentation of whey and malt worts - Chepel, Natalia; Grek, Olena; Krasulya, Olena (My University, 2013)
Results of gas chromatographic studies for definition of by-products of fermentation of whey and malt worts enabled evaluate advantages Zygosaccharomyces lactis 868-K yeast race objectively. Presence of the given yeast race in nutritional medium has a positive effect on producer’s metabolism, thus stimulating biosynthesis or transformation of nutritional medium aromatic substances.
Keywords: by-products of fermentation; побічні продукти бродіння; побочные продукты брожения; lactose fermenting yeast; лактозозброджувальні дріжджі; лактосбраживающие дрожжи; sensory indicators; органолептичні показники; органолептические показатели; кафедра технології молока і молочних продуктів